Trends in the Use of Critical Thinking as Mathematics Learning over the last 20 Years: Analysis Bibliometric - Ariawan, Rezi; Sukestiyarno, Yohannes Leonardus; Pujiastuti, Emi; Sugiman, Sugiman; Zafrullah, Zafrullah (FKIP Universitas Lampung, 2024)
This research aims to analyze research trends on the topic of critical thinking in mathematics learning using bibliometric analysis. By selecting documents in Scopus Database using the PRISMA method, 94 documents were obtained which were analyzed using the R Program and VOSviewer. From the results of the analysis, it can be concluded that research on the Scopus database began in 2004 to 2024 or the last 20 years, with a 3-fold increase in publications in the last 6 years. 2020 was the year with the highest citation impact, namely 130(10.53%) citations. Indonesia stands out as the country with the highest number of publications at 19(20.21%) and number of citations is 145(11.75%). International Journal of Instruction stands out as the source with the highest h-index, namely 5. Universitas Islam Negeri Mataram leads with a total of 8(8.51%) publications. Suparman from the Universitas Pendidikan Indonesia is the author with the highest contribution with an h-index of 5. The article with the highest number of citations of Şendağ et al. (2009) with 241 citations. 39 keywords were obtained which were divided into 7 groups, with the keywords